MINAT BERWIRAUSAHA MAHASISWA INDONESIA DAN CINA - Tur Nastiti; Nurul Indarti; Rokhima Rostiani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
Entrepreneurial intention, defined as a process of information-searching which can be used to achieve a new venture, has been intensively discussed as a contributed factor for those who intended to create a business. This study was purposed to explore predictors of entrepreneurial intention among Indonesian and Chinese students. We quantitavely integrated 241 students that have been used to investigated the relationship of the personality and environmental factors with entrepreneurial intention. As hypothesized, multiple regresson analysis and independent-sample t-test revealed the differences of entrepreneurial intention’s predictors among both countries. Chinese students were mostly affected by need for achievement, locus of control, self-efficacy, and instrumental readiness, while Indonesian students by self-efficacy. Implications toward university and government were discussed.